2020
DOI: 10.1111/eva.13030
|View full text |Cite
|
Sign up to set email alerts
|

Contrasted patterns of local adaptation to climate change across the range of an evergreen oak, Quercus aquifolioides

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 100 publications
2
20
0
Order By: Relevance
“…This interpretation is consistent with the significant proportion of variation explained by the genotypic factor for both the symmetric components of leaf shape and leaf size traits (~ 20% in Table 3, using a more complete set of nSSRs), when using dbRDA to jointly test geographic, genetic, and climatic factors on morphological variation. Besides, Du et al (2020) also showed strong patterns of isolation by distance overall and within lineages, using a few hundred SNP markers, consistently with genetic drift and limited gene flow between distant populations.…”
Section: Possible Impact Of Lineages Geographical Isolation On Leaf Size and Shape Variationmentioning
confidence: 65%
See 2 more Smart Citations
“…This interpretation is consistent with the significant proportion of variation explained by the genotypic factor for both the symmetric components of leaf shape and leaf size traits (~ 20% in Table 3, using a more complete set of nSSRs), when using dbRDA to jointly test geographic, genetic, and climatic factors on morphological variation. Besides, Du et al (2020) also showed strong patterns of isolation by distance overall and within lineages, using a few hundred SNP markers, consistently with genetic drift and limited gene flow between distant populations.…”
Section: Possible Impact Of Lineages Geographical Isolation On Leaf Size and Shape Variationmentioning
confidence: 65%
“…In the WSP-HDM group of populations, divergent selection pressures were also recently suggested to interpret molecular signals of differentiation at particular drought-stress related candidate genes (Du et al 2020). This could be linked to the observation that climatic variables explained a significant part, although relatively low, of the symmetric components of leaf shape variation across the species range (Table 3, 7.1% and 3.5% of total variance for marginal and conditional dbRDA tests respectively).…”
Section: Impact Of Environmental Pressures On Leaf Shape and Size Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Landscape genomics provides unprecedented insights into understanding the mechanism of adaptive variation of tree species by dissecting the impacts of environmental variables and landscape characteristics on their adaptive evolution ( Browne et al, 2019 ; Pina-Martins et al, 2019 ; Borrell et al, 2020 ; Du et al, 2020 ; Zhao et al, 2020 ). Common challenges, such as the sampling strategies and using only a single analysis for detecting adaptive signatures, still exist in landscape genomic studies although many reviews discuss the abovementioned topics ( Balkenhol et al, 2019 ).…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Adaptive responses from standing genetic variation in response to rapidly changing environments is a much faster process than mutations (Barrett & Schluter, 2008; de Lafontaine et al., 2018). Thus, local populations of widespread tree taxa that experience relatively warm and dry summer conditions in some portions of the species range may already contain in situ genotypes that are better adapted to drought stress relative to variants present in other regions (Du, Wang, Wang, Ueno, & de Lafontaine, 2020). Such molecular variants represent useful sources of genetic variation for managing populations to enhance resiliency to future climate shifts (Christmas et al., 2016) and could be potential targets for assisted gene flow to mitigate maladapted populations (Aitken & Whitlock, 2013).…”
Section: Introductionmentioning
confidence: 99%